UKRAINIAN LEGAL SYSTEM’S FEATURES OF DEVELOPMENT AND FUNCTIONS - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
The purpose: the article is focused on the analysis of the historical development of the Ukrainian legal system and functioning of the country’s modern legal system. It has been proved that the legal system of Ukraine was formed on historically established legal customs and traditions, legal culture, domestic legal opinion and national law. in this aspect, the legal system can be regarded as an objectively formed set of legal phenomena inherent in a particular country. Survey methods: in this work it had been used the dialectical method of cognition, general scientific and special-legal methods. The basis of the methodology in this study is the systematic approach by which a particular object is considered as a multidimensional phenomenon, which consist of various elements, the relations between them form a relatively sustainable structure of the legal system and provide it’s integrity. Results: provided justifications for the necessity of forming a complex concept of the Ukrainian legal system, which would contain all the characteristics of law-making in the country. However, it was determined that the basis of the legal system, it’s foundation, has been the legal thinking, which at the same time one of the elements of the legal system Discussion: the search for ways to improve functional directions of the development of the Ukrainian legal system; European integration vector for the development of the Ukrainian legal system, which leads to the convergence of the Ukrainian and European law.